2020
DOI: 10.1136/gpsych-2020-100206
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hyperprolactinemia induced by risperidone and olanzapine and their correlations with plasma glucose and lipids

Abstract: BackgroundHyperprolactinemia is a common adverse reaction in patients with schizophrenia who take antipsychotic drugs; it often leads to treatment non-compliance in patients and has an adverse effect on their prognosis.AimsThis study aimed to explore the risk factors of elevated prolactin (PRL) caused by risperidone (RIS) and olanzapine (OLZ) and the relationship between PRL and fasting plasma glucose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While these associations are only applicable to higher levels of PRL within the physiological range, high PRL levels in the non-physiological range due to prolactinoma or treatment with antipsychotic drugs have consistently been shown to unfavourably affect metabolic parameters [ 15 , 16 ]. A pathologically higher PRL level in patients with T2DM in a few studies has also been shown to be associated with increased diabetic complications, insulin resistance, and metabolic syndrome [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these associations are only applicable to higher levels of PRL within the physiological range, high PRL levels in the non-physiological range due to prolactinoma or treatment with antipsychotic drugs have consistently been shown to unfavourably affect metabolic parameters [ 15 , 16 ]. A pathologically higher PRL level in patients with T2DM in a few studies has also been shown to be associated with increased diabetic complications, insulin resistance, and metabolic syndrome [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, antipsychotics are linked with increased neurological and metabolic adverse effects in young patients 26 , 27 , though strategies exist to lessen these effects 20 , 27 . Hyperprolactinemia is a clinically significant adverse effect of risperidone treatment in both adults 28 , 29 and, putatively, adolescents 30 . Clinical manifestations such as gynecomastia and galactorrhea represent potential concerns.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are articles published on the analysis of the data in this study, and a pharmacodynamic model has been established to quantify the time-efficacy relationship of antipsychotic drugs. [31][32][33] Contributors WY and SH are responsible for the project implementation and the writing of the paper. JH is responsible for the project implementation and ethical review.…”
Section: Discussionmentioning
confidence: 99%